Legal Regulation of Waste Management in Ukraine on the Way to European Integration - Kidalov, Serhii; Vitiv, Vitaliy; Golovko, Liudmyla; Ladychenko, Viktor (European Journal of Sustainable Development, 2020)
The article is devoted to the research of problems of adaptation of Ukrainian legislation to the norms of EU law. The environmental well-being of the population depends on the legal regulation of waste management and the role of government agencies in controlling these activities. Particular attention in this scholarly work is paid to the overriding objective of learning from the experience of the EU member states by creating a qualitative mechanism and achieving the main result – improvement of national legislation by implementing European standards in the sphere of waste management. Keywords: EU waste policy, EU law, waste management, municipal waste, adaptation of Ukrainian legislation to EU law